Adult learning in the aftermath of job loss: Exploring the transformative potential - Terri Deems Laswell (Adult Education Research Conference, 1994)
A qualitative design was used to explore the experience of job loss and to gain insight into the ways in which adults learn and change within this context. Findings reveal incidental learning and new meaning perspectives as central components of the job loss experience. This study contributes to a growing empirical exploration of transformative learning and re-frames the experience of job loss in terms of opportunities for fundamental change and transformation.